Is Islam against modernity? - Omer, Spahic (AboutIslam, 2019)
Modernity is an exclusively Western concept that has no equivalent in other cultures and civilizations. Linguistically, most world languages adopted the same concept with slight etymological variations. Those which did not, provided their own alternatives, which, in essence, were closest single-word interpretations of the term’s meaning and substance. In Arabic, translation of the term oscillates between the words of hadathah and ‘asriyyah, with different forms of the words of tajdid, tatwir and bid’ah being occasionally used in order to cast more light on some secondary nuances of the term of modernity. Islam is the final revelation revealed to the final messenger to mankind, Muhammad (peace and blessings be upon him). As such, inspired by its finality, two of Islam’s underlining characteristics are its universality and applicability till the end of this earthly life. Their essence is summed up as follows. In its revealed and perennial sources, the Holy Qur’an and Sunnah of the Prophet, Islam contains all the essential spiritual and moral truth required my humankind to live honourable, consequential and accountable lives. Just as the world has its universal and constant physical laws, it also has its universal and constant spiritual and moral ones. While the former permeates and is inscribed on the “pages” of the physical aspects of life, the latter permeates all levels of existence and is inscribed on the pages of the revealed Qur’an and the Prophet’s Sunnah. Both sets of laws are indispensable for living a successful and happy life, individually and collectively. Doing so furthermore means striking a delicate balance between the two poles of existence. Resorting to either pole at the expense of the other, upsetting thereby the intended ontological equilibrium and harmony, leads to devastating consequences at all levels of the human presence on earth, which will be proportionate to the level of imbalances and tensions.